Buddhist Integrative Leadership in Change - ฉนฺทปาโล, พระครูสาทรปริยัติคุณ; นันทเพ็ชร, กฤษฎา (Journal of Educational Review Faculty of Education in MCU, 2018)
Organizations can proceed in the right direction and achieve the goal because of the leaders. The leaders will lead organizations and members to achieve the goals set. That the organizations will be prosperous or failed depends on the leaders. The leaders who live a life according to Buddhist principles can bring prosperity, peace, goodness, and stability to organizations and society. To put the Buddhist principles into practice as Buddhist leadership is the role that society should recognize more than the worldly leadership.